PENANGGULANGAN PENGGUNAAN NARKOTIKA DAN PSIKOTROPIKA DI KALANGAN REMAJA DI KOTA PAREPARE - Alias Mangnga P (Jurnal Ilmiah Administrasita', 2014)
Purpose of this research is to know form of abuse of narcotic and psychotropical at adolescent, factors influencing abuse of narcotic and psychotropical and effort done to overcome. Result of research indicates that influenced by environmental factor, lack of attention of old fellow, inharmonious family, lack of adherence believes in and available of goods market to be illegal.